2005
DOI: 10.1016/j.ejcts.2005.08.029
|View full text |Cite
|
Sign up to set email alerts
|

Adventitial inversion technique without the aid of biologic glue or Teflon buttress for acute type A aortic dissection

Abstract: The adventitial inversion technique provides an excellent immediate hemostasis and facilitates thrombotic closure of the proximal and the distal false lumen in the treatment for acute type A aortic dissection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 24 publications
1
38
0
Order By: Relevance
“…Since this method's initial introduction by Floten et al, 1) a few clinical studies have confirmed that it is a feasible and safe technique providing successful exclusion of the false lumen from antegrade flow at the anastomotic level. 2,3) However, there are some experimental reports suggesting that, due to the extrinsic coagulation pathway via exposed adventitial collagen and tissue factor, inverted adventitia may elicit thrombus formation with subsequent embolization, 4) although the thrombogenicity of inverted adventitia has not been tested clinically to our knowledge. Wishing to address this technique's advantages and its potential complications, we integrated this method with our method of telescopic graft insertion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since this method's initial introduction by Floten et al, 1) a few clinical studies have confirmed that it is a feasible and safe technique providing successful exclusion of the false lumen from antegrade flow at the anastomotic level. 2,3) However, there are some experimental reports suggesting that, due to the extrinsic coagulation pathway via exposed adventitial collagen and tissue factor, inverted adventitia may elicit thrombus formation with subsequent embolization, 4) although the thrombogenicity of inverted adventitia has not been tested clinically to our knowledge. Wishing to address this technique's advantages and its potential complications, we integrated this method with our method of telescopic graft insertion.…”
Section: Discussionmentioning
confidence: 99%
“…One current method is the adventitial inversion technique, firstly reported by Floten et al 1) Recent studies confirmed this technique's feasibility and safeness, demonstrating that it facilitates thrombotic closure of the false lumen more effectively than other methods. 2,3) However, the intraluminal adventitia supposedly carries the risk of thrombus formation with subsequent embolization, which has been shown in experimental studies in small-caliber anastomoses. 4) To prevent this serious complication and improve hemostasis at the anastomotic site, we have developed a novel technique involving adventitial inversion employing, previously described by us, graft telescopic insertion.…”
Section: Introductionmentioning
confidence: 99%
“…The anastomosis of the aorta and vascular graft are generally performed using the adventitial inversion technique. 8,9) …”
Section: )mentioning
confidence: 99%
“…The ascending aorta was replaced in the usual manner. 3 The two saphenous vein grafts were relocated on the Dacron graft by the button technique using 5-0 polypropylene sutures (Fig. 3).…”
Section: Casementioning
confidence: 99%